Regio- and stereoselective synthesis of new spiro-isoxazolidines via 1,3-dipolar cycloaddition - Nafâa Jegham; Amira Bahi; Nizar El Guesmi; Yakdhane Kacem; Béchir Ben Hassine (Arabian Journal of Chemistry, 2017)
New spiro-isoquinolinediones were prepared by regio- and stereoselective 1,3-dipolar cycloaddition of (E)-4-arylidene-N-methyl-isoquinoline-1,3-dione derivatives 1a–d with C-aryl-N-phenylnitrones 2e–g. NMR studies confirmed that only one regioisomer was formed selectively in the majority of cases. Regioselectivity of the reaction was established by 1H and 13C NMR assignments. The stereochemistry of spirannic compounds 3a–l and 4a–c has been corroborated by means of DFT calculations. The structures of all the products were characterized thoroughly by NMR and elemental analyses.